The Trend of “Multicultural Education” in 2021-2022: Bibliometrics Mapping in Scopus - Elihami, Elihami; Melbourne, Mohd. (Jurnal Pendidikan Progresif, 2022)
The trend of ‘multicultural education’ in 2021-2022: Bibliometrics mapping in Scopus. Objectives: the purpose this research explained the trend of “multicultural education” by using bibliometrics in 2021-2022. By conducting documentary research and bibliometric analysis of papers obtained in the Scopus database between 2021 and 2022, the following study was undertaken to examine research trends and the global scientific field's general view on multicultural education. Methods: the VOSviewer software was used to examine 91 documents, including articles, books, and book chapters. The research method is the qualitative approach through VOS viewer. Findings: the keywords (KW+) were used as the analytical units in this work, and bibliometric maps were created from them utilizing co-word analysis, grouping approaches such as clustering and visualization techniques, and database analytics. Conclusion: the study reveals the importance of enhancing those experiences and methods aimed at creating educational experiences that allow for the development of cognitive and socio-emotional abilities, as well as encouraging the construction of peace and preventing violence through education and increasing its visibility in the scientific community. Keywords: multicultural education, education, multicultural, Bibliometrics.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202204